Do Income Smoothing, Forward-Looking Disclosure, and Corporate Social Responsibility Decrease Information Uncertainty? - Firmansyah, Amrie; Irwanto, Andry (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to examine the effect of income smoothing, forward-looking disclosure, and corporate social responsibility on information uncertainty. Information uncertainty is defined as value ambiguity or a level of estimation of a firm’s value carried out by investors who have a lot of company information. Investors interpret information as a level of certainty of a company in the future. The method uses quantitative methods. The sample uses 51 manufacturing companies listed on the Indonesian Securities Exchange before January 1, 2009. The result suggests that income smoothing is not associated with information uncertainty. Accounting information provided by the company is not used as a basis for investors in making investment decisions. Furthermore, forward- looking disclosure and corporate social responsibility are negatively associated with information uncertainty. Information disclosed by the company relating to the condition of the company in the future, and investors consider corporate social responsibility as a positive matter.